Simultaneous optimization of enzyme activity and quaternary structure by directed evolution - Vamvaca, Katherina (Cold Spring Harbor Laboratory Press, 2005)
Natural evolution has produced efficient enzymes of enormous structural diversity. We imitated this natural process in the laboratory to augment the efficiency of an engineered chorismate mutase with low activity and an unusual hexameric topology. By applying two rounds of DNA shuffling and genetic selection, we obtained a 400-fold more efficient enzyme, containing three non-active-site mutations. Detailed biophysical characterization of the evolved variant suggests that it exists predominantly as a trimer in solution, but is otherwise similarly stable as the parent hexamer. The dramatic structural and functional effects achieved by a small number of seemingly innocuous substitutions highlights the utility of directed evolution for modifying protein–protein interactions to produce novel quaternary states with optimized activities.